Uncovering Integrated STEM Attitudes and Dimensional Correlations in Education: Mengungkap Sikap STEM Terintegrasi dan Korelasi Dimensi dalam Pendidikan - Ummah, Munfiathul; Shofiyah, Noly (Indonesian Journal of Education Methods Development, 2024)
This study investigates the attitudes towards STEM among junior high school students at Muhammadiyah Sidoarjo in Indonesia, focusing on exploring the degree of attitude towards STEM and examining the relationship between STEM dimensions. Using a survey method with 85 students from a population of 326, the research found that students' attitudes were most pronounced in the integrated STEM dimension, followed by engineering, technology, science, and mathematics. However, correlations between certain STEM dimensions and STEM itself were inconsistent, highlighting nuances in students' perceptions. These findings contribute to enhancing STEM education strategies, particularly in schools with integrated STEM-based learning, and suggest avenues for further research in broader educational contexts. Highlight: Examining STEM attitudes in Muhammadiyah Sidoarjo's junior high. Analyzing correlations between STEM dimensions and their implications. Enhancing STEM education strategies in Indonesia's educational context. Keyword: STEM education, Attitude assessment, Muhammadiyah Sidoarjo, Junior high school, Indonesia